The Effect of Shocks on the Current and Future Behavior of Sudan Economy: Autoregressive Moving-average Approach - Ahmed, Ahmed Elsheikh M.; Elsheikh, Leena Ahmed (European Scientific Journal, ESJ, 2020)
This paper attempts to achieve two core objectives. Firstly, it aims to synthesize the information contained in the different expenditure components of GDP for developing a set of Autoregressive Moving-Average (ARMA) models to examine the effect of shocks on the current and subsequent cyclical deviations of Sudan real GDP from what is trending. Secondly, it aims to compare the intensity of those cyclical deviations within the reviewed period (1970-2010) and outside it. ARMA models of different orders are experimented to distinguish, empirically, whether the effect of shocks is transient or permanent and lasts for a long period of time. The major result is that the lingering effect of shocks is permanent causing intensified deviation from the trend outside the reviewed period.